نظام البلديات في الجزائر: دراسة في الاختلالات وآفاق الإصلاح - محمد المرتاجي سعيداوي (Universty Of El-oued جامعة الوادي, 2026)
يحظى إصلاح نظام البلديات في الجزائر باهتمام متزايد خاصة في الآونة الأخيرة، فالبلدية هي أكثر مؤسسة يحتك بها المواطن و يتفاعل معها، كما أنها تضطلع بأدوار تنموية هامة على المستويين المحلي والوطني، ويتجلى زيادة اهتمام السلطة السياسية في الجزائر بقضايا إصلاح نظام البلدية من خلال الجهود المتكررة لإدراج تعديلات بهدف تحسين أداء البلديات لاختصاصاتها، غير أن نظام البلديات في الجزائر لايزال يواجه تحديات عويصة خاصة في المجالات التالية: الديمقراطية المحلية ، مالية البلديات، التسيير الإداري، التقسيم الاقليمي للبلديات، فواقع الديمقراطية المحلية على مستوى البلديات يفصح عن اختلالات سلبية كثيرة تتطلب حلول واقعية تتيح للمواطنين التعبير عن إرادتهم بحرية و تسمح للمنتخبين بممارسة صلاحياتهم بفاعلية، كما أن وضع مالية البلديات يكشف عن ضعف كبير في مداخيل البلديات في مقابل توسع لصلاحيتها ما يستدعى إعادة النظر في تسيير مالية البلديات ومنحها حرية أكبر للاستثمار في مواردها الذاتية، وفي ما يتعلق بتسيير وإدارة البلديات يتبين أن هذه الأخيرة تواجه مشكلات متعددة خاصة في جانبي التوظيف والتكوين، كما أن ظاهرة الفساد الإداري تعد المعرقل الأكبر لجهود التنمية المحلية، وبالتالي فإن إصلاح هذه التحديات يستدعي مراجعة وإعادة تقييم لفاعلية برامج التوظيف والتكوين المحلي، وإرساء آليات جديدة لمحاربة ظاهرة الفساد الإداري، علاوة على ذلك فإن التقسيم الإقليمي للبلديات في الجزائر يحتاج لإعادة النظر وأن يكون هذا التقسيم مبني على أسس علمية تضمن الاستغلال الأمثل للإمكانات والموارد المحلية على مستوى كل إقليم بلدي، وبالتالي فإن تشخيص هذه التحديات وصياغة حلول واقعية لها سيساهم بشكل فعال في تقوية أداء البلديات للأدوار المنتظرة منها بما يرتقى لمستوى تطلعات المواطنين Abstract The reform of the municipal system in Algeria has garnered increasing attention recently, as the municipality represents the primary institution for citizen interaction and engagement. Furthermore, it plays a pivotal role in driving local and national development. The political authority's commitment to reforming this system is evident through repeated legislative efforts aimed at enhancing the performance of municipalities in executing their mandates. Nevertheless, the Algerian municipal system continues to face formidable challenges, particularly in the areas of local democracy, municipal finance, administrative management, and territorial division, the current state of local democracy reveals significant structural imbalances that necessitate realistic solutions to empower citizens to express their will freely and enable elected officials to exercise their powers effectively, Regarding municipal finance, there is a stark disparity between limited revenues and expanding responsibilities, which calls for a fundamental restructuring of financial management and granting municipalities greater autonomy to invest in their self-generated resources, in terms of administrative management, municipalities suffer from multifaceted issues, particularly in recruitment and professional training. Moreover, administrative corruption remains a major impediment to local development. Addressing these challenges requires a comprehensive evaluation of recruitment effectiveness and local training programs, alongside the establishment of robust mechanisms to combat corruption. Additionally, the territorial division of municipalities in Algeria requires a revision based on scientific criteria to ensure the optimal utilization of local resources. Diagnosing these challenges and formulating pragmatic solutions is essential to strengthening municipal performance and meeting the growing expectations of citizens.
أطروحة دكتوراه تخصص تخصص: التنمية والجماعات المحلية في كلية الحقوق والعلوم السياسية
Keywords: نظام البلديات؛ اللامركزية المحلية؛ التحديات؛ التنمية المحلية؛ آفاق الإصلاح.; Municipal System; Local Decentralization; Challenges; Local Development; Reform Perspectives.